Negative Consumption Behavior in the Era of Social Media - Heikkilä, Annika Sofia (2024)
The impact of social media on consumption is significant, as content continually prompts consumption through social media. Social media content creates continuous impulses for purchases filled with material and various experiences. Thus, it is easy to fall into negative consumption behavior and increased consumption through social media. Therefore, it is crucial to gain a better understanding about the factors behind negative consumption behavior and how social media affects negative consumption behavior. The aim of this study was to provide answers to the research question: How does social media affect negative consumption behavior? The sub-problems of the study were: What are the drivers behind negative consumption behavior? How does social comparison on social media affect consumer consumption behavior? How does social media reinforce the Diderot effect? This study examines the impact of social media on negative consumption behavior.